Effectiveness and safety of bictegravir/emtricitabine/tenofovir alafenamide fumarate for people with ultra-high viral load of HIV-1: a retrospective real-world cohort study - He, Xiangxi; Xie, Xiaoxin; Fu, Yanhua; He, Jinhong; Luo, Xingxing; Long, Hai (Frontiers in Virology, 2025)
BackgroundThis study evaluated the effectiveness and safety of bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) in treatment-naïve adults with HIV-1 and an ultra-high viral load (uVL; HIV-1 RNA ≥500,000 copies/mL)—a population at high risk for suboptimal outcomes.MethodsA retrospective cohort study was conducted among 75 patients initiating BIC/FTC/TAF. The modified intent-to-treat (mITT) group included all patients, while the per-protocol (PP) group comprised 58 individuals who completed 96 weeks of follow-up. Virological suppression, immunological response, safety, and resistance were assessed.ResultsVirological suppression rates in the PP group were 98.3% at week 48 and 96.6% at week 96, compared to 74.7% and 78.7% in the mITT group—a gap largely due to non-clinical dropouts. Immunological recovery was significant, with median CD4+ counts increasing from 61.5 to 326.0 cells/μL (p < 0.001). No treatment-emergent resistance was detected. Adverse events were mild (6.9%).ConclusionBIC/FTC/TAF is highly effective and safe for adherent uVL patients, demonstrating rapid viral suppression and immune recovery. However, real-world effectiveness is significantly limited by socioeconomic barriers, highlighting the need for improved programmatic support to enhance retention and treatment access.